Data Sheet 1_An institutional review of perioperative outcomes in pediatric bone marrow donors. A retrospective study.docx - Kavitha C. Raghavan (22679006) (2025)
Background During hematopoietic stem and progenitor cell collection from the bone marrow under anesthesia, pediatric donors are exposed to potential complications including hypotension, pain, blood transfusion, endotracheal intubation risks, prone positioning injuries, and postoperative nausea and vomiting (PONV). We evaluated the overall incidence and severity of adverse events to identify opportunities to improve perioperative outcomes for this unique population. Methods With institutional review board approval, all donors under 18 years of age who had bone marrow harvest under general anesthesia between 2010 and 2024 at our institution were included in this retrospective study. Autologous donors and donors whose cells were collected by apheresis without anesthesia were excluded. Results The study included 61 donors with a mean age of 9.62 years, mean donor/recipient weight ratio of 1.57, mean harvest volume of 14.2 mL/kg donor weight, and mean fasting duration for clear liquids and solids of 9.31 and 11.3 h, respectively. Twenty-nine (47.5%) experienced at least 1 adverse event. 10 (16.4%) donors experienced at least 1 cardiovascular adverse event. Out of ten episodes of significant hypotension events, 4 donors required vasopressors intraoperatively, 2 experienced dizziness in the post-anesthesia care unit (PACU), and 4 experienced symptomatic hypotension after discharge from the PACU. One infant required blood product transfusion. Six donors (9.8%) experienced post-operative nausea vomiting (PONV), and 7 others (11.5%) experienced post-discharge vomiting. There was one overnight admission, 1 readmission, and 2 unanticipated visits. Conclusions This single institution study highlights improvement opportunities for the perioperative care of pediatric bone marrow donors. We propose strategies to optimize preoperative fasting, intraoperative analgesia, and antiemetic prophylaxis and recommend a procedure-specific intravenous fluid replacement calculator, and admission and discharge criteria for bone marrow donors.